2012
DOI: 10.1039/c1em10783f
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and fate of androgens, estrogens, glucocorticoids and progestagens in two different types of municipal wastewater treatment plants

Abstract: The occurrence and fate of fourteen androgens, four estrogens, five glucocorticoids and five progestagens were investigated in two different types of wastewater treatment plants (Plant A: activated sludge with chlorination, and Plant B: oxidation ditch with UV) of Guangdong province, China. 14, 14, and 10 of 28 target compounds were detected in the influent, effluent and dewatered sludge samples with the concentrations ranging from below 1.respectively. The concentrations of total androgens (1554-1778 ng L À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 49 publications
5
74
0
Order By: Relevance
“…21−23 However, for progestagens, most studies were focused on their concentrations in different treatment units and their aqueous phase removal rates in WWTPs, as well as their concentrations in receiving waters. 3,5,12,13,16,24 Only one study by Chang et al 13 reported the degradation kinetics of some progestagens with aerobic sludge. Up to now, there have been no detailed studies on biodegradation of the synthetic progestogen norgestrel, which has been detected at concentrations up to 10.8 μg/L in wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21−23 However, for progestagens, most studies were focused on their concentrations in different treatment units and their aqueous phase removal rates in WWTPs, as well as their concentrations in receiving waters. 3,5,12,13,16,24 Only one study by Chang et al 13 reported the degradation kinetics of some progestagens with aerobic sludge. Up to now, there have been no detailed studies on biodegradation of the synthetic progestogen norgestrel, which has been detected at concentrations up to 10.8 μg/L in wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Progestins have been detected in surface waters [9][10][11] and wastewaters [12][13][14]. Norgestrel was found in surface water at concentrations up to 22 ng L À1 [11] and in municipal wastewater-treatment plant effluents at concentrations up to 11 ng L À1 [13]. In addition, norgestrel is often used to control the pregnancy time of animals in the livestock industry and has detected in wastewaters of swine and dairy cattle farms with concentrations up to 10 800 ng L…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation tank is always used as a pretreatment process in WWTPs and makes less contribution in reducing steroids in wastewater Liu et al, 2012). Most steroids in the sedimentation tank effluents of farms C1 and C2 showed some concentration reduction compared with loafing area wastewater, but some still had high concentration levels, which even exceeds mg/L (Table 3).…”
Section: The Removal Of Steroids In Dairy Cattle Farmsmentioning
confidence: 99%
“…Various steroids have been reported in different environmental matrices, such as in wastewater treatment plants (WWTPs) (Liu et al, , 2012Ying et al, 2009), aquatic environments Zhao et al, 2010), livestock farms (Lange et al, 2002), and wastewater irrigated soils . Humans (e.g., human urine and feces) and livestock (e.g., animal manure and wastewater) are the main sources of steroids releasing into the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation